Prevention Of Fraud In The Service Provider Selection Process At Riau Regional Office Of The Construction Service Procurement Implementation Center Ministry Of Public Works And Housing - Rahmarta, Vandy; Nirwana, Nirwana; Syamsuddin, Syamsuddin (Jurnal Ekonomi, 2024)
Study This aims to identify potential fraud prevention strategies in the election process for provider service construction at the Implementation Hall Selection of Construction Services (BP2JK) for the Riau Region, Ministry of PUPR. Through qualitative influencing factors​ , Fraud prevention according to internal employees in the Riau Region BP2JK work unit was researched comprehensively. Analysis results show that fraud prevention requires a holistic approach involving​ commitment leaders in applying Firm and transparent internal policies. Additionally, regular employee education and training, strict supervision with mechanism reporting, and team collaboration are critical factors in preventing cheating: internal solid policies, implementation technology like e-procurement systems for increased transparency, and employee education sustainability. Understanding applicable rules and regulations also plays a vital role in fraud prevention efforts. Recommendation For increased effort: Fraud prevention includes enhancement training and awareness about ethics, development of technology information For overcoming gap security, collaboration inter-team supervision and audit, and enhancement transparency in the selection process provider service. With these steps, It is hoped that BP2JK Riau Region will be able to do this. Keep going, increase integrity and effectiveness in operating his duties, and create an environment free of work​ from practice cheating.